Particularity and universality: The role of religious and nationality values in the formation of political values of university students - Diah Kusumawati; Rachma Ida; Budi Suharjo (Faculty of Social and Political Science, Universitas Airlangga, 2023)
The discourse of Islamism in Indonesia in the last ten years has been closely associated with the term radical Islam. In previous studies among students, this term has been often contrasted with nationality values concerning democracy, tolerance, and support for the Unitary State of Indonesian Republic (Known as NKRI). This study aimed to find the particularity and universality of individual political values among university students. This research argued that religious and nationality values become part of individual political values. This research used a quantitative method involving 208 respondents of university students at a state university. The data were analysed using cluster and discriminant analysis to identify the discursive conditions of university students. This research generated three clusters. Cluster 1 is the political tolerant, social media savvy of politics, financially unsatisfied. Cluster 2 is the non-political religious. Cluster 3 is the political religious enthusiast, social media savvy of politics. The three clusters have diversities in terms of interest in politics, the use of social media for political issues and activities, and religious values. However, the three clusters have similarities in nationality values. This research also shows that there is a relationship between political values and the faculty; a correlation between political values with political figures and political parties.